Green Energy Conversion Systems - Kumar A.; Kumar S.; Saket R.K.; Rajendran R.; Eslamian S. (My University, 2025)
This chapter develops a technological solution for waste management at the source. A device containing a soil microbial fuel cell (MFC) is designed for reliable renewable energy production using kitchen waste. The innovative methodology and constructed green energy conversion system produces ‘eco-friendly’ electricity by capturing energy produced by naturally occurring microbial metabolism of organic materials such as food scraps, manure and plant waste. Biomass that may be used includes municipal solid waste and agricultural by-products. The electricity generated by soil MFCs can be utilized immediately by USB devices. The developed system removes and sequesters carbon dioxide and methane gas, creating a clean, environmentally responsible supply of multiple power types. The overall process provides an option for current power generation and alleviates the need for fossil fuels. Green energy conversion systems enable domestic power generation and create the possibility for reduced dependence on imports for energy needs. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.